PENGARUH KEPUTUSAN INVESTASI DAN KEPUTUSAN PENDANAAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Fitria, Fitria; Putri, Anne; Rahmawaty, Dian; Nurfitriyenny, Nurfitriyenny; Supriyanita, Rina (Komunitas Manajemen Kompetitif, 2025)
Abstract: Investment decisions and financing decisions are financial decisions taken by a manager that affect the value of the company. In the industrial sector, manufacturing companies experience a problem, namely the value of the company, which sometimes increases, sometimes decreases, and even always decreases. In fact, maximising company value is very important for a company because maximising company value also means maximising the main objectives of the company. This study aims to test the effect of investment and financing decisions on company value in consumer goods manufacturing companies listed on the Indonesia Stock Exchange. This study uses a quantitative approach. The research population is consumer goods manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2020-2021. The sampling technique uses a purposive sampling technique, and 58 samples were obtained. The analysis test tool used is SmartPLS 3.0. with the SEM (Structural Education Modelling) analysis method. The test results of this study indicate that investment decisions affect company value as well as investment decisions affect company value. Keywords: Investment Decisions, Financing Decisions, Firm Value.